Comparison between itrauterine aspiration cytology and endometrial biopsy. - Marahatta, Rita
ABSTRACT: ABSTRACT: This is a hospital based prospective study conducted at Tribhuvan University Teaching Hospital during a period of 6 months in women aged 40years and above with abnormal uterine bleeding. After the age of 40 years the chances of malignancy in women will be higher, so the study was based on the patients above 40 years. Patients with known cause of bleeding were excluded from the study. Total of 50patients were identified and recruited in the study. The main objectives of the study were to find out the commonest endometrial pathology among those women and also to find out the diagnostic accuracy of intrauterine aspiration cytology over endometrial biopsy. Patients were explained about the procedure and written consent was taken. History taking and through general and systemic examination were carried out and patients were subjected for the procedure. The procedure was planned any time after 15 days of last vaginal bleeding except to those patients who were having continuous bleeding for a month or more, they were subjected for the procedure at their first visit. The questionnaires were filled up accordingly. Each and every patient was subjected for intrauterine aspiration with karman cannula and syringe followed by endometrial biopsy with small Sherman curette. The sample were preserved and sent to pathology department and reports were collected. No anesthesia was used during the procedure. Among 50 patients with abnormal uterine bleeding 34% were in the age group of 50-55 years and 32% in the age group of 40-45 years. Eight patients (16%) were post-menopausal and remaining 42 patients (82%) were pre-menopausal. The main type of abnormal uterine bleeding was menorrhagia (34%) followed by metrorrhagia (18%). Three patients were having blood-mixed discharge and remaining with combination of all. There were 17 patients (34%) with poliferative endometrium and same number of patients with endometrial hyperplasia. All endometrial hyperplasia were in pre-menopausal age group. Three cases (6%), 1 with tubercular endometritis (2%) and remaining 9 patients (18%) were having secretory endometrium on endometrial biopsy. No case of endometrial carcinoma was found in theis study. All biopsy reports were matched with intrauterine aspiration cytology reports . They were well matched in all cases except in one case in which the report of cytology said few endometrial cells inadequate for reporting . So the sensitivity of the intrauterine aspiration cytology found to be 98% with positive predictive value of 100%, so it can be used in the diagnosis of endometrial pathology instead of endometrial biopsy.